Contribution of the Community Health Volunteers in the Control of Buruli Ulcer in Benin - Barogui, Yves Thierry; SOPOH, GHISLAIN E.; JOHNSON, ROCH CHRISTIAN; de Zeeuw, Janine (My University, 2014)
Background: Buruli ulcer (BU) is a neglected tropical disease caused by Mycobacterium ulcerans. Usually BU begins as a painless nodule, plaque or edema, ultimately developing into an ulcer. The high number of patients presenting with ulcers in an advanced stage is striking. Such late presentation will complicate treatment and have long-term disabilities as a consequence. The disease is mainly endemic in West Africa. The primary strategy for control of this disease is early detection using community village volunteers. Methodology/Principal Findings: In this retrospective, observational study, information regarding Buruli ulcer patients that reported to one of the four BU centers in Be´nin between January 2008 and December 2010 was collected using the WHO/ BU01 forms. Information used from these forms included general characteristics of the patient, the results of diagnostic tests, the presence of functional limitations at start of treatment, lesion size, patient delay and the referral system. The role of the different referral systems on the stage of disease at presentation in the hospital was analyzed by a logistic regression analysis. About a quarter of the patients (26.5%) were referred to the hospital by the community health volunteers. In our data set, patients referred to the hospital by community health volunteers appeared to be in an earlier stage of disease than patients referred by other methods, but after adjustment by the regression analysis for the health center, this effect could no longer be seen. The Polymerase Chain Reaction (PCR) for IS2404 positivity rate among patients referred by the community health volunteers was not systematically lower than in patients referred by other systems. Conclusions/Significance: This study clarifies the role played by community health volunteers in Be´nin, and shows that they play an important role in the control of BU.
Keywords: Benin; control; community health